Lone survivor : the eyewitness account of Operation Redwing and the lost heroes of SEAL Team 10 - Luttrell, Marcus; Robinson, Patrick, 1939- (New York : Back Bay Books, 2008)
The leader, and only survivor, of a team of U.S. Navy SEALs sent to northern Afghanistan to capture a well-known al Qaeda leader chronicles the events of the battle that killed his teammates and offers insight into the training of this elite group of warriors.
To Afghanistan...in a Flying Warehouse -- Baby Seals...and Big Ole Gators -- A School for Warriors -- Welcome to Hell, Gentlemen -- Like the Remnants of a Ravaged Army -- 'Bye, Dudes, Give 'Em Hell -- An Avalanche of Gunfire -- The Final Battle for Murphy's Ridge -- Blown-up, Shot, and Presumed Dead -- An American Fugitive Cornered by the Taliban -- Reports of My Death Greatly Exaggerated -- "Two-two-eight! It's Two-two-eight!" -- Epilogue: Lone Star -- Afterword: Patrick Robinson -- Never Forget
Originally published in hardcover by Little, Brown and Company, 2007.
Keywords: Luttrell, Marcus; United States. -- Navy. -- SEALs -- Officers; Afghan War, 2001- -- Campaigns; Afghan War, 2001- -- Personal narratives, American